Between "lecture" and "exploration"! Learning culture in Arabic as a second language (Romano-arabica, 2025)
This paper seeks to answer the following questions: What is “culture” in the field of second language acquisition? What are the challenges of learning it? What aspects of culture should we teach? And how can culture be integrated into learning materials and presented to learners?The paper employs a descriptive-analytical methodology based on the researcher's practical experience, as well as references to other studies to support the arguments presented. It begins with a brief overview of the major shifts in the field of second language acquisition, to pinpoint the place of the cultural component within it. It then attempts to define the role of culture in Arabic as a second language instruction. Furthermore, it proposes a framework for what cultural content should be presented to learners at each proficiency level, accompanied by suggestions on how to present and integrate it with the language.The paper emphasizes the necessity of incorporating culture into Arabic language learning materials and courses, through design and implementation that contribute to enhancing linguistic proficiency. While the paper does not showcase examples of learner outputs in cultural activities, it does offer some applied models for cultural learning strategies. The paper encourages cultural learning and exploration, advocating for learners to explore the culture themselves, rather than relying solely on classroom-based cultural instruction.
Keywords: Culture; Proficiency; Cultural Competence; Communicative Language Teaching; ACTFL